Association of Hepatitis ‘C’ Virus Infection (HCV) and Liver Enzymes Abnormalities Among Apparently Healthy Individuals in Jos North, Plateau State, Nigeria - Frama, Ishaku; Zakka, Sheyin; Isa, Bigwan Emmanuel; Jiking, Gutau Fipo; Victoria, Ishaya (African Journal of Medicine, Surgery and Public Health Research, 2025)
Hepatitis C virus (HCV) infection remains a significant global health concern, particularly in resource-limited settings such as Nigeria, where routine screening and early diagnosis are often lacking. This study investigated the seroprevalence of HCV infection and its association with liver enzyme abnormalities among apparently healthy individuals in Jos North, Plateau State. A total of 180 participants were screened for anti-HCV antibodies using rapid diagnostic kits (Labtrust, UK) and confirmed by ELISA (Qingdao Hightop Biotech, China), yielding a seroprevalence rate of 5.0%. Liver function was evaluated through measurement of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels to assess hepatic injury. Among seropositive individuals, 88.9% showed elevated ALT and 77.8% had elevated AST levels. While these elevations were more frequent in HCV-positive participants than in seronegative controls, the differences were not statistically significant (ALT: p = 0.064; AST: p = 0.061). However, effect size analysis (Glass’s Δ > 1.4) indicated clinically meaningful enzyme elevations, suggesting subclinical liver injury. Multivariate logistic regression controlling for demographic variables did not reveal a statistically significant predictive relationship between HCV status and elevated liver enzymes, likely due to sample size limitations and potential multicollinearity. These findings underscore the silent progression of HCV-related hepatic damage in asymptomatic individuals and highlight the need for proactive screening and biochemical monitoring. Public health initiatives promoting widespread, cost-free HCV testing and liver function assessment are essential for early detection, reducing disease burden, and preventing long-term complications such as cirrhosis and hepatocellular carcinoma.